Dari Kali Code ke Ruang Digital: Meneguhkan Filsafat Memanusiakan Manusia Romo Mangun sebagai Etika Publik Generasi Kontemporer - Yanto Yanto (Fakultas Teologi, Universitas Sanata Dharma, 2026)
Many of the ethical and sustainability challenges we face today, from the environmental crisis to the impacts of digital disruption, share a common root: we often compartmentalize nature, humanity, and technology. This complex problem demands a perspective that views everything as interconnected. This qualitative research aims to analyze the urgency of Integral Ecology as a transformative ethical framework and to ground it in the Pancasila Philosophy as a foundation in the Digital Age. I highlight the figure and thought of Father Y.B. Mangunwijaya as a practical model for implementing Social Ecology and Human Rights (HR). Using a literature review and philosophical analysis method, this research addresses three main questions. First, how does the concept of Integral Ecology bridge the environmental crisis and digital disruption? Second, what are the core moral values of Pancasila that must be applied in Public Ethics? Third, how can Father Mangun's spirit of